Experimental evidence that feral cats cause local extirpation of small mammals in Australia's tropical savannas. Issue 6 (17th September 2014) - Frank, Anke S. K.; Johnson, Chris N.; Potts, Joanne M.; Fisher, Alaric; Lawes, Michael J.; Woinarski, John C. Z.; Tuft, Katherine; Radford, Ian J.; Gordon, Iain J.; Collis, Mary‐Anne; Legge, Sarah
Summary: Small mammal species are declining across northern Australia. Predation by feral cats Felis sylvestris catus is one hypothesised cause. Most evidence of cat impacts on native prey comes from islands, where cat densities are often high, but cats typically occur at low densities on mainland Australia. We conducted a field experiment to measure the effect of predation by low‐density cat populations on the demography of a native small mammal. We established two 12·5‐ha enclosures in tropical savanna in the Northern Territory. Each enclosure was divided in half, with cats allowed access to one half but not the other. We introduced about 20 individuals of a native rodent, Rattus villosissimus, into each of the four compartments (two enclosures × two predator‐access treatments). We monitored rat demography by mark‐recapture analysis and radiotracking, and predator incursions by camera surveillance and track and scat searches. Rat populations persisted over the duration of the study (18 months) in the predator‐proof treatment, where we detected no predator incursions, but declined to extinction in both predator‐accessible compartments. In one case, cat incursions were frequently detected and the rat population was rapidly extirpated (<3 months); in the other, cat incursions were infrequent, and the population declined more gradually ( c . 16 months) due to low recruitment. We detected no incursions by dingoes Canis dingo, the other mammalian predator in the area. Synthesis and applications . This is the first study to provide direct evidence that cats are capable of extirpating small mammals in a continental setting, in spite of their low population densities. This finding supports the hypothesis that predation by feral cats is contributing to declines of small mammals in northern Australia. The conservation management of native small mammals in northern Australia may require intensive control of cat populations, including large cat‐free enclosures. Abstract : This is the first study to provide direct evidence that cats are capable of extirpating small mammals in a continental setting, in spite of their low population densities. This finding supports the hypothesis that predation by feral cats is contributing to declines of small mammals in northern Australia. The conservation management of native small mammals in northern Australia may require intensive control of cat populations, including large cat‐free enclosures.